Gestão ambiental da implantação de sistemas de transmissão de energia elétrica : estudo de caso: interligação norte/sul - Pires, Lorena Fornari de Ary (2005)
Electric energy is important to achieve the economic growth that is necessary for the improvement of life worldwide, although it is clear that in order to implement these projects certain impacts may be caused on the environment. Therefore reassuring the importance of the Electric Sector in keeping the Planet s health since it is the responsible for the implementation of such projects. In order to achieve both economic growth and environmental protection it is necessary to follow a sustainable development and create instruments through which it can be reached more easily. One of the most useful instruments is the Environmental Management. The main object of this dissertation is to study the Environmental Management in the Brazilian Electric Sector; most specifically related to the transmission systems (linear constructions with peculiar environmental impacts). The research strategy is the Case Study and the project selected was the North/South Interconnection I, transmission system with a total length of 1276 km, crossing different Brazilian regions with different social-environmental characteristics that demanded complex management actions, from its planning until the commercial operation. In order to guide the analysis theoretical and conceptual propositions were developed and they are composed by the rules and policies that regulate the Environmental Management both national and internationally. Since it is a very specific sector, it was necessary to present their characteristics, as well as the institutional and legal implications upon its actions. The strategic context of the sector s political/institutional reformulation was high lighted, as well as the deep changes occurred and the effects on the Environmental Management. The final valuation was made relating the theoretical and conceptual propositions, the Electric Sector specific characteristics and the management actions observed during the implementation of the North/South Interconnection I. As a conclusion, it is proposed strategies that will enable further development of Environmental Management model for transmission systems implementation, in accordance with the Brazilian Electric Sector new political/institutional scenario.